2016
DOI: 10.1161/circoutcomes.116.003086
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Interventions to Reduce Preventable Hospital Readmission After Percutaneous Coronary Intervention

Abstract: Abstract-Hospital readmissions are common and costly and, in some cases, may be related to problems with care processes. We sought to reduce readmissions after percutaneous coronary intervention (PCI) in a large tertiary care facility through programs to target vulnerabilities predischarge, after discharge, and during re-presentation to the emergency department. During initial hospitalization, we assessed patients' readmission risk with a validated risk score and used a discharge checklist to ensure access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Recommendations for improvement should include establishment of hospital-based approaches such as medication checklists [41]. Information technology should be integrated to support decision-making and allows in-hospital prescribing to be followed up at discharge [42].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for improvement should include establishment of hospital-based approaches such as medication checklists [41]. Information technology should be integrated to support decision-making and allows in-hospital prescribing to be followed up at discharge [42].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as low-risk chest pain is often the presentation leading to readmission after PCI (13,14,23,24), improved triage of post-PCI patients to identify the appropriate diagnostic and treatment pathway for these individuals may hasten evaluation and lead to safe discharge from the emergency department. Tanguturi et al demonstrated that a multi-dimensional approach towards readmission reduction utilizing a validated questionnaire to identify patients at high risk for readmission after PCI with subsequent targeted interventions in this group resulted in an absolute decline in readmissions from 9.6% to 5.3% over a 4 year period at one institution (26). A discharge checklist was used to ensure high risk patients had the appropriate discharge medications and close follow-up (26).…”
Section: What Can Be Done About Readmissions After Pci?mentioning
confidence: 99%
“…Tanguturi et al demonstrated that a multi-dimensional approach towards readmission reduction utilizing a validated questionnaire to identify patients at high risk for readmission after PCI with subsequent targeted interventions in this group resulted in an absolute decline in readmissions from 9.6% to 5.3% over a 4 year period at one institution (26). A discharge checklist was used to ensure high risk patients had the appropriate discharge medications and close follow-up (26). These higher risk patients were additionally shown educational videos on chest discomfort and heart failure, and upon re-presentation to the emergency room, their outpatient cardiologist was notified electronically with early cardiology assessment encouraged, and triage decisions made according to a risk stratification algorithm developed (26).…”
Section: What Can Be Done About Readmissions After Pci?mentioning
confidence: 99%
See 1 more Smart Citation
“…We wish to thank our patient for consenting to this report and the many cardiovascular specialists who contributed to his recovery utilizing a novel risk stratification algorithm designed to reduce preventable readmissions after percutaneous coronary interventions [18]. …”
mentioning
confidence: 99%